Reading the Entrails - Charles Conrad, Norman (University of Calgary Press, 1999)
Before the fall of Imperial Rome, priests cast the guts of sacrificial animals on the temple floor, claiming to be able to divine the future from these entrails. By probing the remains of Alberta's past sacrifices (reading the entrails), the author believes we might dimly see an apparition of Alberta's future. This controversial book vividly portrays the history of land and life in Alberta from the Ice Ages to the present. Making no apologies for his criticism of government, regulators, and large corporations, Conrad aims to strike a discussion at all levels by presenting his arguments intensely. For those interested in natural history, the environment, and the future of Alberta's ecological resources, this provocative book is essential reading.